(untitled) (Research, Society and Development, 2022)
With the growth of the pharmaceutical industry in recent years, the generation of waste and effluents from the increase in the production process has increased significantly, and these can cause serious damage to the environment and society when not treated correctly. The final destination of pharmaceutical waste and effluents is a relevant issue for public health due to the different pharmacological properties of medicines that will inevitably become waste and effluents, and which must receive specific treatments because, due to their characteristics, they can be hazardous to health. and the environment, requiring special care, especially in terms of treatment and disposal. For this, there are legal guidelines that, although some are not very specific, serve as guides for companies to comply, and non-compliance is subject to penalties, including imprisonment of those responsible and fines. In addition, today, the image of companies is also closely related to care for the environment and society, being considered an investment, not a cost, all care related to these aspects. And so that industrial waste and effluents do not have negative impacts on the environment, specific treatments are applied to the different types of waste and effluents generated by each industry, each of which must adapt to the legal guidelines that apply to its process. Effluents treatments are divided into physical, chemical, and biological, and the combination of two or more is widely used.